The Historical Context of the Woodhouse Commission - Easton, Brian (Victoria University of Wellington Law Review, 2003)
The Woodhouse Report provides an instructive model for effective advocacy, in that its proposals aimed to solve a clearly defined social problem: meeting the needs of accident victims in an equitable and comprehensive fashion. Moreover the Report presented its solution as a cost-effective way of meeting broader compensation needs, by making existing economic resources go further. This paper argues that the Woodhouse model achieved success largely because of its problem-based clarity and sensitivity to cost efficiency. It also places the Woodhouse treatment of personal injury litigation in a larger historical pattern of evolution in common law.